Incidence of Malignancies Among Patients With Chronic Hepatitis B in US Health Care Organizations, 2006–2018 . (17th January 2022) - Spradling, Philip R; Xing, Jian; Zhong, Yuna; Rupp, Loralee B; Moorman, Anne C; Lu, Mei; Teshale, Eyasu H; Schmidt, Mark A; Daida, Yihe G; Boscarino, Joseph A; Gordon, Stuart C
Abstract: Hepatitis B virus (HBV) infection causes hepatocellular carcinoma but its association with other cancers is not well established. We compared age-adjusted incidence of primary cancers among 5773 HBV-infected persons with US cancer registries during 2006–2018. Compared with the US population, substantially higher incidence among HBV-infected persons was observed for hepatocellular carcinoma (standardized rate ratio [SRR], 30.79), gastric (SRR, 7.95), neuroendocrine (SRR, 5.88), cholangiocarcinoma (SRR, 4.62), and ovarian (SRR, 3.72) cancers, and non-Hodgkin lymphoma (SRR, 2.52). Clinicians should be aware of a heightened potential for certain nonhepatic malignancies among hepatitis B patients, as earlier diagnosis favors improved survival. Abstract : Among patients with chronic hepatitis B in 4 US health care organizations, the incidence of several nonliver cancers (gastric, neuroendocrine, cholangiocarcinoma, ovarian, and non-Hodgkin lymphoma) was substantially higher compared with the US population.